Prayer practices among Palestinian Christians in Occupied Palestinian Territory - Parkkinen, Mari Johanna (Approaching Religion, 2018)
Arab Palestinian Christians face many challenges living in the Occupied Palestinian Territory; restrictions of movement, a poor employment situation and rising emigration. According to previous research, religion and prayer provide strength and hope in the midst of the ongoing conflict. This research has used qualitative methods and the data was collected in the occupied Palestinian Territory in February–April and November 2017. Thirty-five participants were interviewed about their practice of prayer. The interviews were semi-structured. The aim of this paper is to examine how prayer is utilised among the Palestinian Christians to cope in stressful life situations and how prayer types are utilised across generations. Content analysis revealed four prayer types: petitionary, ritualistic, meditative and thanksgiving. The results suggest that prayer is major coping device and the utilisation of prayer varies across the generations.